Remote Work Revolution: Examining the Impact of Hybrid Work Models on Employee Engagement and Productivity - Candra, Candra; Reska Rahmatullah, Jhon Fernos, (Pascasarjana STIE Amkop Makassar, 2024)
This study investigates the impact of hybrid work models (HWM) on freelancers’ engagement, productivity, work-life balance (WLB), and job satisfaction (JS) on the Upwork platform. Using a quantitative research design, 100 active freelancers from Upwork-related communities on Facebook and Twitter were randomly selected to participate in an online survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (Smart PLS). The results reveal that hybrid work models significantly improve freelancers' work-life balance and job satisfaction, which, in turn, positively affect their engagement and productivity. Specifically, the study found significant indirect effects of HWM on engagement and productivity through WLB and JS. These findings suggest that while hybrid work models do not directly influence freelancer performance, they play a crucial role in enhancing job satisfaction and maintaining a balanced work-life environment, which are key drivers of freelancer engagement and productivity. This research provides valuable insights for optimizing work arrangements on digital platforms to foster greater well-being and performance among freelancers. Keywords: Hybrid Work Models, Freelancers, Engagement, Productivity, Work-Life Balance, Job Satisfaction